Deconstructing the Archetypal Mirror of Godot in Ali Abdul-Nabi Al-Zaidi’s “A Second Death” - Al-Dhalimee, Enas (Al-Adab Journal, 2025)
People's waiting which is related essentially to the idea of a Savior, is part of the collective consciousness that has developed itself to an archetype, and this archetype has become like a mirror against which people measure their chances of survival. In the twentieth century theatre, the process of waiting rarely spares Samuel Beckett's Waiting for Godot as an emblematic example, though the character of Godot has become prone to be manipulated into different characterizations that are basically deconstructing the idea of waiting. Therefore, the aim becomes how to excavate man's ability to make some change by one’s own self through paths than passive waiting even if this aspiration for change was within the realm of death.The Iraqi playwright, Ali Abdul-Nabi Al-Zaidi employs in his play A Second Death, a similar dramatic archetypal inheritance. His use of archetypes cluster to constitute a Lacanian mirror through which humanity alludes itself for salvation. Al-Zaidi tries to smash this archetypal mirror, helping his audience to reconstruct themselves away from waiting for a savior.